PERAN KOMUNIKASI BISNIS ISLAM DALAM PENINGKATAN PENJUALAN E-COMMERCE SYARIAH DIKOTA MEDAN - Pratami, Arifa; Hadi, Muhammad; Iyonu, Mentari Ariesta (Program Studi Akuntansi, 2022)
In the current era of globalization and technological advances, it has a major influence on people's lifestyles and economic activities, including in fulfilling household and personal needs and desires. As is the case in the behavior of buying and selling goods online, one of which is through e-commerce or other sales services, Indonesia, which is the largest Muslim country in the world, provides opportunities for every company to create innovations such as in terms of providing e-commerce services. Particularly in the nature of sharia e-commerce, which are currently increasingly in demand by the public, such as Shoppe Berkah, Tokopedia Salam and Lazada Amanah. This study examines the increase in sales of Islamic e-commerce with Stuctural Equation Modeling (SEM) analysis. This research is built on the basis of ethics and Islamic business communication principles which explain that the exchange of messages or information with other parties within the business sphere must be based on Islamic rules. This study found that variables that have an influence on increasing sharia e-commerce sales, namely people's purchasing power and implementation of sharia contracts and Islamic business communication variables have no significant effect on increasing sharia e-commerce sales.